Soil Heat Flux Studies in the Bare Red Laterite Soil During Winter and Summer Months at Bangalore - Rao, G Ramakrishna; Ramamohan, R V; Rao, B V Ramana (Annals of Arid Zone, 2016)
The soil heat fluxes at the surface layers of the bare red laterite soils at Bangalore are reported. A gradual increase in positive heat flow and net flow of heat is noticed from January to May. The negative heat flow is maximum in April when the moisture content is less and more in May when the moisture content is more. The duration of negative heat flow is found to be about 14 hours in a diurnal heat flow cycle. A shift in the heat flow cycle is noticed with the march of summer. In general there is gain of heat by the soil during all the months of observation.